2020
DOI: 10.1080/19942060.2020.1803971
|View full text |Cite
|
Sign up to set email alerts
|

Potential of kernel and tree-based machine-learning models for estimating missing data of rainfall

Abstract: In this study, two kernel-based models were used which include Support Vector Regression (SVR) and Gaussian Process Regression (GPR) and were compared with two tree-based models that are M5 and Random Forest (RF) for estimating missing monthly precipitation data in Antakya, Dortyol, Iskenderun and Samandag stations, which are the important precipitation stations in the Eastern Mediterranean region, Turkey. For this purpose, firstly 10% random precipitation data were assumed as missing data for the period 1980-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…A further challenge with bias correction is the availability of daily streamflow data for the given timeline. Fortunately, this problem is not encountered in this study, although previous research has demonstrated the validity of applying a machine learning technique to interpolate missing data [70]. Additionally, bias correction was performed for river discharge strictly based on its historical datasets, which invites future studies to incorporate other hydrological parameters.…”
Section: Uncertainities and Limitationsmentioning
confidence: 99%
“…A further challenge with bias correction is the availability of daily streamflow data for the given timeline. Fortunately, this problem is not encountered in this study, although previous research has demonstrated the validity of applying a machine learning technique to interpolate missing data [70]. Additionally, bias correction was performed for river discharge strictly based on its historical datasets, which invites future studies to incorporate other hydrological parameters.…”
Section: Uncertainities and Limitationsmentioning
confidence: 99%
“…SVM and the SVR model are the two primary categories of SVM models. A SVM model is used to classify data into multiple classes, while an SVR model is employed for prediction purposes (Sattari et al. , 2020).…”
Section: Modeling Of Wedm Processmentioning
confidence: 99%
“…SVM and the SVR model are the two primary categories of SVM models. A SVM model is used to classify data into multiple classes, while an SVR model is employed for prediction purposes (Sattari et al, 2020). Regression is used to obtain an appropriate hyperplane for the utilized data (Smola and Sch, 2004).…”
Section: Support Vector Regressionmentioning
confidence: 99%
“…The approaches considered were the sparse model for linear regression estimation (Predictor 1) and Random Forest Decision Tree (Predictor 2) due to their various benefits mentioned in numerous researches. [15][16][17] Predictor 1-Linear regression is a statistical approach where a target function is linear and depends on features as the input. All input attributes as real numbers and represented as:…”
Section: Mathematical Modeling Of the Machine Learning Algorithmmentioning
confidence: 99%